Crustaceans composition in sandy beaches of Sepetiba Bay, Rio de Janeiro, Brazil - Ricardo Cardoso; Felipe Meireis; Gustavo Mattos (Check List, 2011)
A crustacean survey was made in Sepetiba bay, Rio de Janeiro state, southeastern Brazil. Twelve sandy beaches were sampled on five islands in this embayment. A total of 3024 individuals were collected, belonging to 21 species, which are grouped in 16 families, seven infraorders, seven suborders, and four orders. Isopods, followed by amphipods and tanaids, showed the highest abundance, amounting to over 92% of the dominance of crustaceans. The main species were Excirolana armata, Excirolana braziliensis (isopods), Atlantorchestoidea brasiliensis (amphipod), and Monokalliapseudes schubarti (tanaid), which together accounted about 80% of crustaceans of the beaches studied. Excirolana braziliensis had the highest frequency. The majority of species found are typical of sandy beaches, with large spatial distribution.